PENGARUH METODE PEMBELAJARAN GAMIFIKASI TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD PADA MATA PELAJARAN PKN SD INPRES KASSI-KASSI - Wilda; Nurilmi; Dwi Aktifa Putri; Zahra Inayah; Nabila Arjuni Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of gamification learning methods on fifth-grade elementary school students' learning motivation in Civics Education (PKN) at Kassi-Kassi Elementary School. This study used a quantitative method with a pre-experimental design (one group pretest-posttest), where the experiment was conducted in one class with the same subject. Data were collected through learning motivation questionnaires administered before (pretest) and after (posttest) the implementation of the gamification method, supported by observation and documentation. The results showed an increase in student learning motivation after the implementation of gamification, as indicated by an increase in the average motivation score on the posttest compared to the pretest. Thus, it can be concluded that the gamification learning method has a positive influence on fifth-grade students' learning motivation in Civics.